(untitled) (UNED Research Journal, 2019)
Introduction: the squirrel Sciurus variegatoides is one of the most abundant species of squirrels in Central America, yet little is known about its reproduction. Objective: to determine the reproductive cycle of S. variegatoides in an agricultural area of Costa Rica. Methods: monthly (Dec. 1986 to Jan. 1988), I collected 10 animals at Hacienda Curú, Paquera, Costa Rica. I used scrotum presence, testicle size and length of the uterine horns to assess maturity. The reproductive cycle was based on pregnancy, lactation, courtship, nest construction, and proportion of subadults. Results: I collected a total 135 squirrels; sex ratio was 1,7 males per female; and 22% were subadults, both for males and females. I captured the pregnant females from December to June and represented 42% of the adult females. February and April were marked by courtship and an increase in the construction of nests. I collected lactating females from June to September, when I captured more subadults. Conclusion: There was no evidence of reproductive activity in October and November.